2012
DOI: 10.1179/1351000212y.0000000005
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress as a cofactor in spinocerebellar ataxia type 2

Abstract: Spinocerebellar ataxia type 2 (SCA2) is a redox-sensitive neurodegenerative disease affecting the cerebellum, fibre connections in the cerebellum, the peripheral nervous system, and extracerebellar central pathways. Currently, Cuba has the highest reported global rate for this disease. The aim of this review article is to summarize and discuss the current knowledge about evidence of oxidative stress during SCA2. Recent reports have suggested that ataxin 2 and other related factors contribute to the redox imbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…Oxidative stress has been suggested to be implicated in the pathogenesis of numerous neurodegenerative diseases, including hereditary ataxias [12]. Many studies have been conducted to validate the therapeutic roles of antioxidants in ARCAs [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been suggested to be implicated in the pathogenesis of numerous neurodegenerative diseases, including hereditary ataxias [12]. Many studies have been conducted to validate the therapeutic roles of antioxidants in ARCAs [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This emphasizes the importance of DUB activity during the recovery from oxidative stress, particularly as redox regulation of the DUBs themselves can therefore determine the duration of stress granule retention, depending on the speed of DUB oxidation reversal. Furthermore, both stress granule formation and oxidative stress have been implicated in neurological disorders such as amyotrophic lateral sclerosis and spinocerebellar ataxia type 2, and DUBs could therefore be a common element between both of these factors ( 25 , 222 , 223 , 224 , 225 ).…”
Section: Cellular Consequences Of Redox Regulation Of Dubsmentioning
confidence: 99%
“…It was reported in the literature that the developing cerebellum is highly vulnerable to the damaging effects of the reacting oxygen species, and the structural changes in the PCs, their dendrites, granule cells, astrocytes, microglia, neuronal axons, and oligodendroglia are observed in the induced oxidative stress [57]. The cerebellar oxidative stress-related alterations typical for SCA2 patients can be related to the altered homeostasis of the different elements in the serum or blood samples [58,59]. Thus, it was reported that the levels of copper, manganese, zinc, and vanadium are disturbed in the blood of SCA2 patients [58].…”
Section: Molecular Changes Underlying the Pc Lossmentioning
confidence: 99%